Young Salafi-niqabi and hijrah:agency and identity negotiation - Yuyun Sunesti; Noorhaidi Hasan; Muhammad Najib Azca (Indonesian Journal of Islam and Muslim Societies, 2018)
This article analyzes the life of young millennial Salafi-niqabi in Surakarta and their strategies in dealing with power relations in their everyday lives. Studies on Salafi in Indonesia have focused more on global Salafimovements, power politics, links with fundamentalist-radical movements, state security and criticism of Salafi religious doctrine. Although there are several studies that try to portray the daily life of this religious group, the majority of previous studies focused on formal institutions and male Salafi. Very few studies have addressed the lives of Salafi women. This is likely due to the difficulty of approaching this group because of their exclusivity, and their restrictions on interacting with the outside world. Using Macleod’s theory of ‘accommodating protest’ within the